A memória da família - Marinho, Maria de Fátima (2019)
The representation of the family world, with several generations' testi-monies, implies both a public and a personal point of view. Often, family affairs are also, in a way, small incidents of great historical mutations. At present, and in Portugal, we still find this kind of novel, which, as a rule, attracts readers greedy to rediscover experiences lived or imagined. The present essay studies a novel published in 1995, where dead characters pre-sent the family plot, speaking of past episodes, rarely objective and not obeying the rigid chronology, but signifying the family life they want to remember